Analysis Of Plasma Farmers Satisfaction With The Implementation Of The Partnership Between KUD Wisma Tani and Plasma Farmers In Air Panas Village, Pendalian IV Koto District, Rokan Hulu District - Anggun Nirmala Sari; Sischa Febriani Yamesa Away; Kusmiati (Universitas Pasir Pengaraian, 2024)
The agricultural sector used by the Indonesian population is plantations. Palm oil and rubber plantations are one of the leading sectors in Rokan Hulu Regency, where the community fulfills its economic needs from these commodities. Farmers in Air Panas Village switched from cultivating rubber to oil palm because rubber production was no longer optimal, but farmers faced limited capital, equipment and lack of expertise so they formed a partnership with KUD Wisma Tani under the guidance of PTPN V. This research aims to analyze the level of satisfaction of plasma farmers on the performance of partnership implementation, knowing the service attributes that are important to improve and maintain and knowing the implementation of the partnership between KUD Wisma Tani and plasma farmers. The research location was determined purposively in Air Panas Village. The method used was simple random sampling with a sample of 79 people. Data was collected through interviews, observation and documentation. The data analysis used in this research is descriptive analysis. The research results show that farmers are very satisfied with the implementation of the partnership with a Customer Satisfaction Index (CSI) value of 83.53%. Attributes that are considered important to maintain are the ability of KUD Wisma Tani to provide seeds, the ability to purchase all harvests according to the agreed price, conformity to the physical standards of the seeds provided, all FFB products accommodated by KUD Wisma Tani, suitability of the FFB selling price and payment time for the harvest. , ownership of oil palm plantation land certificates, ability to guarantee the purchase of FFB, seriousness in conveying the aspirations of plasma farmers and seriousness in overcoming pest and disease problems. The implementation of the partnership between KUD Wisma Tani and plasma farmers is established under the guidance of PTPN V involving routine monitoring and evaluation to ensure the achievement of common goals. Â